Diversity of culturable moderately halophilic bacteria producing extracellular hydrolytic enzymes from marine sediments (Bioscience Journal, 2018)
A total of 114 moderately halophilic bacteria were isolated from marine sediment environments. The isolates are belonged to 23 species based on the 16S rRNA sequence analysis. 63, 52, 47, 57, 74, 15 and 4 isolates are able to produce protease, amylase, lipase, pectinase, pulluanase, xylanase, cellulase, respectively. Combined hydrolytic enzyme activity analysis show that 15 strains present 1 hydrolytic activity, 32 strains present 2 hydrolytic activities, 21 strains present 3 hydrolytic activities, 26 strains present 4 hydrolytic activities, 11 strains present 5 hydrolytic activities and 2 strains present 6 hydrolytic activities. Hydrolase activities are widely distributed in a variety of species. The highest rates for production of protease, amylase, lipase, pectinase, pullanase, xylanase and cellulase were observed in species of B. baekryungensis, Hallobacillus sp., B. pumilus, B. megaterium or P. chungwhensis, B. amyloliquefaciens, B. pumilus, B. baekryungensis, respectively. However, the higher activities of protease, pectinase and pulluanase are frequently produced by the species of Halomonas sp. B. amyloliquefaciens or P. chungwhensis, and Vibrio sp. respectively. This investigation show that the diversity of halophilic bacteria from marine sediments could serve as a potential source of hydrolytic enzymes for industrial applications.